Life’s Crucial 9 and psoriasis: a mediation analysis of systemic inflammation response index using NHANES cohort data - Liu, Xinyan; Deng, Qirui; Tang, Hongfeng (Frontiers in Immunology, 2025)
BackgroundPsoriasis is a chronic, recurrent, inflammatory disease. The aim of this study was to investigate the association between the Life’s Crucial 9 (LC9) score and the risk of psoriasis and to examine the mediating role of system inflammation response index (SIRI).MethodsUtilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2009 to 2014, this study employed multifactor logistic regression, restricted triple spline analysis, and various subgroup analyses to evaluate the correlation between LC9 scores and the occurrence of psoriasis. Furthermore, mediation analyses were executed to investigate SIRI’s possible intermediary effect in the linkage between LC9 scores and psoriasis.ResultsThis study included 11,499 US adults with 345 psoriasis patients. In fully adjusted models, a notable inverse relationship was identified between the LC9 score and the prevalence of psoriasis (OR = 0.90, 95% CI: 0.80, 0.99). After adjusting for all covariates, no significant interactions were found in the subgroup analyses. In addition, mediation analysis showed that SIRI mediated the association between LC9 and psoriasis (mediation ratio: 7.02%, p = 0.004).ConclusionsHigher LC9 scores reduce the risk of psoriasis. And, this association was mediated by SIRI. This suggests that we should actively regulate our lifestyles to improve cardiovascular health, thereby preventing and delaying the onset of psoriasis.